Togliatti : vita di un italiano - Prattico, Franco; Anatra, Bruno (Roma : D'Urso Editore, 1964)
Fonds Perrone
Italiaans
Monografie
Keywords: Togliatti, Palmiro; Communistische Partij van Italië; Italië